A study to know the prevalence of genital tuberculosis in female’s pulmonary tuberculosis patients and role of cartridge based nucleic acid amplification test in genital tuberculosis from North India - Kumar, Anand; Singh, Aparjot; Chaudhri, Sudhir; Verma, Sanjay Kumar; Pandey, Kiran; Singh, Mahendra; Kant, Surya (International Journal of Research in Medical Sciences, 2021)
Background: Mycobacterium tuberculosis, most commonly, infects the lungs (pulmonary TB). Most cases of female genital TB (FGTB) are found in premenopausal women, theoretically because an atrophic endometrium provides a poor milieu for mycobacterial growth. Female genital TB generally occurs secondary to pulmonary (commonest) and more common in women with reproductive age group. The present study was designed to know the prevalence of genital tuberculosis in female’s pulmonary tuberculosis patients and role of cartridge based nucleic acid amplification test (CBNAAT) in genital tuberculosis. Methods: The patients of female’s pulmonary tuberculosis were picked up from out-patient and in patients’ section of the hospital at random. After ruling out pregnancy, the endometrial samples were collected from premenstrual endometrium (approximately 2-3 days before menstruation) and were subjected to histopathological examination and CBNAAT. Day 1 or 2 menstrual blood of unmarried females and patients not giving consent for biopsy were taken. Results: Seventy married and 20 unmarried patients of female pulmonary tuberculosis patients were evaluated for genital tuberculosis. The mean age of married population was 29±7.68 years. Cough with expectoration was most common respiratory symptoms and seen in 94% cases. In present study 89% cases were sputum positive and 11% were sputum negative. The percentage of non MDR and MDR TB cases were respectively 95.7 and 4.2% respectively. Among the gynecological symptom’s irregular menstruation, vaginal discharge and pelvic pain were present in 68, 60 and 52% of the study patients respectively. The diagnosis of FGTB by histopathology examination and CBNAAT were 28.6 and 17.1% respectively. Conclusions: In present study FGTB diagnosed by histopathology examination and CBNAAT were 28.6 and 17.1% respectively and which was statistically significant (c2=28.25 and p value=0.00001).